Omics-based analytical approaches for assessing chicken species and breeds in food authentication - Goh, Dirong; Nematbakhsh, Sara; Selamat, Jinap; Pei, Pei Chong; Idris, Lokman Hakim; Nordin, Noordiana; Fatchiyah, Fatchiyah; Abdull Razis, Ahmad Faizal (MDPI, 2021)
Chicken is known to be the most common meat type involved in food mislabeling and adulteration. Establishing a method to authenticate chicken content precisely and identifying chicken breeds as declared in processed food is crucial for protecting consumers’ rights. Categorizing the authentication method into their respective omics disciplines, such as genomics, transcriptomics, proteomics, lipidomics, metabolomics, and glycomics, and the implementation of bioinformatics or chemometrics in data analysis can assist the researcher in improving the currently available techniques. Designing a vast range of instruments and analytical methods at the molecular level is vital for overcoming the technical drawback in discriminating chicken from other species and even within its breed. This review aims to provide insight and highlight previous and current approaches suitable for countering different circumstances in chicken authentication.